FORMULATION AND EVALUATION OF WOUND HEALING ACTIVITY OF LINEZOLID TOPICAL PREPARATIONS ON DIABETIC RATS - Khatri, Sakaram Kashyap; Rathnanand, Mahalaxmi; R., Nikhila (International Journal of Applied Pharmaceutics, 2016)
Objective: The aim of the study is to formulate and evaluate the topical preparations of antibacterial formulation for the treatment of diabetic wound infection. Methods: Different types of topical formulations were prepared and evaluated for in vitro release. The prepared formulations were also tested for its antibacterial activity against the pathogens existing in diabetic wound infection. Based on in vitro drug release and antimicrobial activity, two formulations were selected as optimized formulations. Optimized formulations were tested for wound healing activity in diabetic rats. Results: Based on in vitro drug release and antimicrobial activity two formulations (F8, F10) were selected as optimized formulations. FTIR studies of pure drug and optimized formulation shown absence of any incompatibility between drug and excipients. Optimized formulation shown good physicochemical properties and passed short-term stability study. F8 and F10 formulations were applied to untreated diabetic rats for diabetic wound infection, the rate of wound healing was quite faster. These results indicate that the linezolid semisolid dosage form could provide an adjunctive antimicrobial formulation for the management of diabetic wounds. Conclusion: Further studies are required on chronic diabetic wounds with and without diabetic medications to confirm its effectiveness. Keywords: Staphylococcus aureus, Linezolid, Semisolid dosage forms, Wound healing activity